The United Nations at 80 Years of Existence: The Achievements and Challenges in Global Peace and Security in the 21st Century - Sarki, Usman (Journal of Contemporary International Relations and Diplomacy, 2025)
Lecture Delivered by Ambassador Usman Sarki, Former Deputy Permanent Representative of Nigeria to the United Nations, New York. At the 8th Edition of the Diplomatic Dialogue Series organised by the Department of International Relations and Diplomacy, Afe Babalola University, Ado-Ekiti, Ekiti State, Nigeria